Students with learning disabilities written output, academic performance, attitudes, and writing support system - Ong, Rebecca P. (2008)
The study determined the effects of a writing support system (WSS) on the written output, academic performance, and attitudes of four college-bound grade 12 high school students with learning disabilities. Vygotsky's theory of instruction and his ideas of scaffolding were put into practice. A scoring rubric was used to rate the participants' written output before and during the intervention. In addition, an attitudinal questionnaire towards the WSS was completed by the classroom teacher. The findings showed strong evidence supporting the effectiveness of using the writing support system to the four participants of the study as revealed in their improved written output, increased academic performance and positive attitude towards the writing support system.